Wings of Fire : The Poison Jungle - Book 13 - Sutherland, Tui, 1978- (New York : Scholastic Press, 2019)
Sundew and most of the other LeafWings are nursing a deep hatred for the HiveWings, who have ripped every tree from the surface of Pantala, except those in Poison Jungle where the surviving LeafWings have been hiding, waiting for a dragon clever and powerful enough to exact their revenge--and now they are searching for the jungle's oldest and darkest mystery, one that could destroy them all.
Keywords: Dragons -- Juvenile fiction; Magic -- Juvenile fiction; Secrecy -- Juvenile fiction; Revenge -- Juvenile fiction; Good and evil -- Juvenile fiction; Adventure stories; Dragons -- Fiction; Magic -- Fiction; Secrets -- Fiction; Revenge -- Fiction; Good and evil -- Fiction; Adventure and adventurers -- Fiction; Fantasy; Action and adventure fiction; Adventure fiction